Polarization axis fluctuations in a single mode VCSEL laser at 780nm - Dudzik, Grzegorz; Rzepka, Janusz (Photonics Letters of Poland, 2013)
We present a transmission method to determine the polarization axis fluctuations for VCSEL (Vertical Cavity Surface Emitting Laser). The research is focused mainly on commercial lasers operatingat 780 nm, designed forlaser spectroscopy. The angle fluctuation of the laser linear axis polarization iselaborated to be less than 150 mrad. Measurement errors of this method are studied and calculated. The measurement uncertainty is ?1,4 mrad andthis is equivalent to ? 5? of arc.Changes of the linear polarization axis depending on the laser current and temperaturearepresented. Full Text: PDF References T. Ohtoshi et al., "Dependence of optical gain on crystal orientation in surface?emitting lasers with strained quantum wells", Appl. Phys. Lett.63, 1886 (1994). CrossRef K. Tateno et al., "Growth of vertical-cavity surface-emitting laser structures on GaAs (311)B substrates by metalorganic chemical vapor deposition", Appl. Phys. Lett.70, 3395 (1997). CrossRef O. Tadanaga et al., "An 850-nm InAlGaAs strained quantum-well vertical-cavity surface-emitting laser grown on GaAs (311)B substrate with high-polarization stability", IEEE Photon. Tech. Lett.12, 942 (2000) CrossRef K. Choquette, R. Leibenguth, "Control of vertical-cavity laser polarization with anisotropic transverse cavity geometries", IEEE Photon. Tech. Lett. 6, 40 (1994) CrossRef B. Weigl et al., "High-performance oxide-confined GaAs VCSELs", IEEE J. Sel. Top.Quantum Electron. 3, 409 (1997) CrossRef P. Dowd et al., "Complete polarisation control of GaAs gain-guided top-surface emitting vertical cavity lasers", Electron. Lett. 33, 1315 (1997) CrossRef M. Grabherr et al., "Volume production of polarization controlled single-mode VCSELs", Proc. SPIE,6908, 690803 (2008) CrossRef R. Roy et al., "First-Passage-Time Distributions under the Influence of Quantum Fluctuations in a Laser", Phys. Rev. Lett.45, 1486 (1980) CrossRef J. Martín-Regalado et al., "Polarization switching in vertical-cavity surface emitting lasers observed at constant active region temperature", Appl. Phys. Lett. 70, 3350 (1997) CrossRef M. B. Willemsen et al., "Polarization Switching of a Vertical-Cavity Semiconductor Laser as a Kramers Hopping Problem", Phys. Rev. Lett. 82, 4815 (1999) CrossRef M. B. Willemsen et al., "Anatomy of a Polarization Switch of a Vertical-Cavity Semiconductor Laser", Phys. Rev. Lett. 84, 4337 (2000) CrossRef T. Mukaihara et al., "Excess intensity noise originated from polarization fluctuation in vertical-cavity surface-emitting lasers", IEEE Photon. Technol. Lett. 7, 1113 (1995) CrossRef